Impaired functional vitamin B6 status is associated with increased risk of lung cancer. Issue 12 (4th January 2018) - Theofylaktopoulou, Despoina; Midttun, Øivind; Ueland, Per M.; Meyer, Klaus; Fanidi, Anouar; Zheng, Wei; Shu, Xiao‐Ou; Xiang, Yong‐Bing; Prentice, Ross; Pettinger, Mary; Thomson, Cynthia A.; Giles, Graham G; et al.
Abstract : Circulating vitamin B6 levels have been found to be inversely associated with lung cancer. Most studies have focused on the B6 form pyridoxal 5′‐phosphate (PLP), a direct biomarker influenced by inflammation and other factors. Using a functional B6 marker allows further investigation of the potential role of vitamin B6 status in the pathogenesis of lung cancer. We prospectively evaluated the association of the functional marker of vitamin B6 status, the 3‐hydroxykynurenine:xanthurenic acid (HK:XA) ratio, with risk of lung cancer in a nested case–control study consisting of 5, 364 matched case–control pairs from the Lung Cancer Cohort Consortium (LC3). We used conditional logistic regression to evaluate the association between HK:XA and lung cancer, and random effect models to combine results from different cohorts and regions. High levels of HK:XA, indicating impaired functional B6 status, were associated with an increased risk of lung cancer, the odds ratio comparing the fourth and the first quartiles (OR4th vs . 1st ) was 1.25 (95% confidence interval, 1.10–1.41). Stratified analyses indicated that this association was primarily driven by cases diagnosed with squamous cell carcinoma. Notably, the risk associated with HK:XA was approximately 50% higher in groups with a high relative frequency of squamous cell carcinoma, i.e., men, former and current smokers. This risk of squamous cell carcinoma was present in both men and women regardless of smoking status. Abstract : What's new? Low vitamin B6 status, assessed by circulating pyridoxal 5′‐phosphate (PLP), has been associated with increased risk of lung cancer. Because PLP levels can be influenced by other parameters than vitamin B6 status, the authors analyzed a functional vitamin B6 marker, the hydroxykynurenine:xanthurenic acid ratio (HK:XA). They found that high levels of HK:XA, indicative of functional vitamin B6 impairment, was associated with increased risk of lung.